EVALUATING ENTREPRENEURSHIP TRAINING PROGRAM FOR KEAKSARAAN FUNGSIONAL PROGRAM AT KECAMATAN GUNUNGHALU - Nurlaeni Nurlaeni (IKIP Siliwangi Bandung, 2018)
Keaksaraan Fungional (KF) program faces challenges for its participants still face issues post-program, specifically economic welfare related issues. Various programs have been organised to supplement KF. Among them, is entrepreneurship training and life skills training. This research attempts to evaluate such program held at Desa Pandansari, Kecamatan Gununghalu, specifically at the community of Karya Lestari Community Learning Center (CLC) using the responsive evaluation model. Generally, the program showed positive results and have been successful in engaging its participants to be more responsive when facing economic challenges in daily life.